2020
DOI: 10.1109/access.2020.3024112
|View full text |Cite
|
Sign up to set email alerts
|

Operating Cost Reduction of DC Microgrids Under Real-Time Pricing Using Adaptive Differential Evolution Algorithm

Abstract: Virtual resistance-based droop control is widely adopted as secondary-layer control for gridconnected converters in DC microgrids. This paper presents an alternative usage of the virtual resistances to minimize the total operating cost of DC microgrids under real-time pricing. The total operating cost covers the running cost of utility grids, renewable energy sources (RES), energy storage systems (ESS), fuel cells, and power loss on the distribution lines. An adaptive Differential Evolution (ADE) algorithm is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The energy storage system is introduced to compensate power and alleviate bus voltage fluctuations. (1) According to the analysis in [3], [4], and [7], the converter loss can be simplified as a quadratic function of the output currents of DER as…”
Section: Distribution Loss Modelling Of Ac Microgridmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy storage system is introduced to compensate power and alleviate bus voltage fluctuations. (1) According to the analysis in [3], [4], and [7], the converter loss can be simplified as a quadratic function of the output currents of DER as…”
Section: Distribution Loss Modelling Of Ac Microgridmentioning
confidence: 99%
“…For these voltage-based models, the best reference voltage [4] and the optimal power flow [5], [6] for each der can be obtained to reduce online power loss. To reduce loss, an offline-optimization method [7] is proposed to find the best operating point of the load shedding machine. However, this offline solution only works under very ideal working conditions, with little or no change in parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various optimization approaches applied to microgrids; these include classic and artificial intelligence techniques, such as particle-swarm optimization (PSO) [6], genetic algorithms [7], or adaptive differential evolution algorithms [8]. In [7], the authors formulated an optimal power flow problem using a genetic algorithm to minimize the total operation cost of a DC microgrid while considering real-time pricing.…”
Section: Introductionmentioning
confidence: 99%
“…The total operating cost covered the operation cost of utility grids, renewable energy resources, energy-storage systems, and fuel cells. Similarly, the authors in [8] suggested an adaptive differential evolution algorithm to minimize the operating cost of DC microgrids under real-time electricity prices. In [9], the authors suggested an optimal design and model predictive control (MPC) of a standalone hybrid renewable energy system (HRES).…”
Section: Introductionmentioning
confidence: 99%
“…ith a high penetration of power electronics interfaced distributed energy resources (DERs) in DC microgrid, the distribution loss is an increasingly prominent problem, especially in mediumand long-distance low-voltage networks [1]- [6]. In DC microgrids, distributed secondary control has been widely adopted to achieve voltage restoration [7][8][9], load sharing [9,10], energy balancing [11,12], and power loss reduction [12][13][14], and economic dispatch [15] for DERs However, those conventional distributed secondary control are based on the communication between the two neighboring units, which are vulnerable under cyberattacks [16]. Typical cyber-attacks on the communicationbased hierarchical control are took place in steady-state control variables [17].…”
Section: Introductionmentioning
confidence: 99%